A comparison of lead and steel shot loads for harvesting mourning doves - Brian L. Pierce; Thomas A. Roster; Michael C. Frisbie; Corey D. Mason; Jay A. Roberson (Wildlife Society Bulletin, 2015)
ABSTRACT With approximately 100 million shots fired at mourning doves (Zenaida macroura) annually, it is incumbent on managers to determine whether changes in ammunition will substantially alter harvest metrics or hunter satisfaction. We compared mourning dove harvest metrics for 1 lead (Pb 7½, 32 g) and 2 steel (Fe 7 and Fe 6, 28 g) 12‐gauge ammunition types using a double‐blind field test in central Texas, USA. There were no differences in the number of attempts, or number of shots fired among ammunition types. Hunters were unable to distinguish the ammunition type being used in the field, and we detected no relationship between ammunition type and level of hunter satisfaction. Field analyses detected no difference in doves bagged per shot, wounded per shot, bagged per hit, or wounded per hit among the 3 ammunition types. Necropsy analyses detected no difference in the proportion of birds with through‐body strikes, mean penetration depth of through‐body strikes, or mean embedded pellet depth among ammunition types. Ammunition and choke combinations that produced higher pattern densities yielded more hits per shot and produced more total strikes per bird, resulting in a higher percentage of birds with embedded pellets, more embedded pellets per bird, and a higher proportion of birds with broken legs. All 3 ammunition types retained sufficient lethality to harvest mourning doves under typical hunting conditions. Our results demonstrate that when the ammunition type used provides sufficient lethality for pellets to penetrate vital organs, pattern density becomes the primary factor influencing ammunition performance. © 2014 The Authors. The Wildlife Society Bulletin is published by The Wildlife Society